2015
DOI: 10.1016/j.landusepol.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land tenure arrangements on the adaptive capacity of marginalized groups: The case of Ghana’s Ejura Sekyedumase and Bongo districts

Abstract: Climate change and variability continue to adversely impact on the livelihoods of many, especially agriculture-dependent households, in dryland sub-Saharan Africa. Climate vulnerability is shaped by institutions and socioeconomic processes including land tenure arrangements and infrastructural development. This paper employs a participatory mixed-method approach including household questionnaire surveys, key informant interviews, oral narratives and focus group discussions to understand the dynamics of livelih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 63 publications
3
41
0
1
Order By: Relevance
“…Farm tenure was significant at 5% indicating that farmers who own their farms were more likely to have higher yields than sharecroppers and those managing family farms. This conformed to the priori expectation in Table 1, section 2.6 and in line with the finding of [19] that security and quality of land tenure rights directly affect how resources are used and managed. Also, [20] asserts that farm tenure systems in Ghana are complex and changes over time in response to evolving ecological and socio-economic conditions.…”
Section: Factors Affecting Cocoa Yieldsupporting
confidence: 89%
“…Farm tenure was significant at 5% indicating that farmers who own their farms were more likely to have higher yields than sharecroppers and those managing family farms. This conformed to the priori expectation in Table 1, section 2.6 and in line with the finding of [19] that security and quality of land tenure rights directly affect how resources are used and managed. Also, [20] asserts that farm tenure systems in Ghana are complex and changes over time in response to evolving ecological and socio-economic conditions.…”
Section: Factors Affecting Cocoa Yieldsupporting
confidence: 89%
“…Although land tenure was not cited as a major stressor, recording an overall risk index of 0.06, the results show that the majority of the 11 % that cited this stressor were female. This may be due to the complex land tenure arrangements in northern Ghana (Yaro 2010), which further undermine the adaptive capacity of female farmers (Antwi-Agyei et al 2015). In contrast, the stressors identified by male participants (irrigation and agricultural equipment) reflect the roles of men in many dryland agrarian settings in sub-Saharan Africa, where they typically control assets and resources that could enhance household's adaptive capacity (Naab and Koranteng 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that a registered title could ultimately lead to increased farm productivity and higher income (see Figure 1). Recent research by Philip Antwi-Agyei, Dougill, and Stringer (2015) strongly recommends title registration as a panacea in Ghana. In the light of existing challenges to this view (e.g., Hammond, 2008), it is important to revisit the debate and the evidence in Ghana, starting with the legislation underpinning the drive for titling in the country.…”
Section: Theoretical Basis Of Land Title Registrationmentioning
confidence: 99%